Fellow of the Young Academy of Europe_CLONE - Fyndanis, Valantis (My University, 2026)
It is a great honor for me that I became member of this prestigious European association of top young researchers. Members of the Young Academy of Europe (YAE) are leading young scholars who meet the following eligibility requirements: 1. are outstanding researchers with recognised national/international excellence 2. have a wide interest in science and science policy at the European level 3. have demonstrated leadership abilities (e.g., group leader; principal investigator status; primary supervisor of PhD students) 4. are presently carrying out research in the European Union or an associated country 5. have obtained their PhD ≤12 years ago (with credit given for e.g., childcare: 18 months per child for women, time taken off for men; national service) The nomination package contained (1) an application form, (2) a brief curriculum vitae, including a list of most important publications, (3) a statement of interest indicating, among others, my willingness to actively contribute to the YAE mission, and (4) two letters of nomination by current members of the Academia Europaea from two separate countries, and (5) a copy of my PhD certificate.
Keywords: Humanities